Imaging and spectroscopic analysis of living cells: imaging live cells in health and disease - Conn, Patrick Michael (Methods in enzymology, 2012)
This volume of Methods in Enzymology is the third of 3 parts looking at current methodology for the imaging and spectroscopic analysis of live cells. The chapters provide hints and tricks not available in primary research publications. It is an invaluable resource for academics, researchers and students alike. The second of 3 parts looking at current methodology for the imaging and spectroscopic analysis of live cells. The chapters provide hints and tricks not available in primary research publications. It is an invaluable resource for academics, researchers and students alike